THE EFL STUDENTS' PERCEPTION OF USING WHATSAPP APP GROUP DURING THE PANDEMIC SITUATION - Riza, Nasrul Miftahul; Mustofa, Mutmainnah; Abdillah, Faiz (Universitas Muhammadiyah Metro, 2024)
WhatsApp is a mobile phone application and web-based social network that integrates various features used to communicate with other users, including education, business, and entertainment. This study aimed to investigate EFL students' perspectives on WhatsApp as a medium for teaching and learning during the pandemic. The qualitative descriptive method was used in this study. A total of 30 students from the seventh grade in SMP 13 Jember were included in this study. The questionnaire was designed with both closed-ended and open-ended questions. The Guttman Scale is the format for a closed-ended questionnaire. The open-ended questions allowed participants to freely communicate and express their views and opinions, but there were no possibilities for using WhatsApp in English classrooms during the COVID-19 pandemic. During the COVID-19 epidemic, students' attitudes toward the WhatsApp application in English classes were tested using closed-ended and open-ended questionnaires. The information was gathered using a questionnaire and a phone interview. Following the completion of the research, we will learn how EFL students perceive WhatsApp as an online teaching-learning media during a pandemic. Furthermore, the results of this study that gauged participants' perception of the use of WhatsApp in learning vocabulary show that, generally, participants have positive attitudes towards learning new vocabulary items via WhatsApp. Implications for teaching and future research are discussed.